2022
DOI: 10.3390/foods11071023
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heat Treatment on Cow’s Milk Protein Profiles

Abstract: Milk is a food of high nutritional value processed by heat treatment. Heat treatment of milk is a technological process designed to inhibit the growth of microorganisms and extend the shelf life of products. The heating process directly affects the molecular structure of whey proteins by the process of denaturation. It leads to the formation of a whey protein–casein polymer complex. Based on these facts, milk heat-treatment conditions should be controlled during milk processing. This work focuses on describing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…SDS-PAGE study showed that the band color of the @DEX 5k -BSA faded with prolonged heating (Figure B). Since protein gelation caused by cross-linking creates an insoluble three-dimensional network, this prevents depolymerization by SDS and β-mercaptoethanol and restricts penetration through the running gel, resulting in lighter bands. , Thus, the heat treatment-induced cross-linking between BSA resulted in gelation with time. Correspondingly, the improved stability of @DEX 5k -BSA under heat treatment was confirmed by the retarded drug release and reduced variation in particle size (PS) and polydispersity index (PDI) (Figure C–E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SDS-PAGE study showed that the band color of the @DEX 5k -BSA faded with prolonged heating (Figure B). Since protein gelation caused by cross-linking creates an insoluble three-dimensional network, this prevents depolymerization by SDS and β-mercaptoethanol and restricts penetration through the running gel, resulting in lighter bands. , Thus, the heat treatment-induced cross-linking between BSA resulted in gelation with time. Correspondingly, the improved stability of @DEX 5k -BSA under heat treatment was confirmed by the retarded drug release and reduced variation in particle size (PS) and polydispersity index (PDI) (Figure C–E).…”
Section: Resultsmentioning
confidence: 99%
“…Then the blood was sampled from the aortaventralis and detected as in previous reports. 46 After centrifugation, 100 μL plasma was mixed with 20 μL butyl acetate and 380 μL cyclohexane. The mixture was centrifuged at 5000 rpm for 10 min at 4 °C and the supernatant from each aliquot (1 μL) was injected into the GC-MS system for assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of micronutrients is unaffected by pasteurization, but important fatty acids, water-soluble vitamins, and hormones are affected by sterilization [4]. Čurlej et al [5] found that the heat treatment significantly positively affects the whey protein denaturation process and whey protein-casein complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…Čurlej et al. [5] found that the heat treatment significantly positively affects the whey protein denaturation process and whey protein‐casein complex formation.…”
Section: Introductionmentioning
confidence: 99%